Prevention and control of gas and spontaneous coal combustion coupled disasters during mining withdrawal with roof cutting and pressure relief - Zehao Jing; Xihua Zhou; Yanchang Li; Gang Bai; Lianchao Zhang (Case Studies in Thermal Engineering)
The gob-side entry retaining mining mode with roof cutting and pressure relief (GERRCPR) has improved coal mining efficiency but increases airflow leakage as the retaining roadway is exposed to the gob. During the withdrawal period, significant changes in the gob's flow field occur, and leftover coal becomes prone to prolonged oxidation and heat buildup, leading to potential coupled disasters of gas and coal spontaneous combustion (CDGCSC). This study focuses on preventing and managing CDGCSC at the South 5–1201 gob at Daxing Mine during the withdrawal period. Numerical simulations were used to identify optimal gas and fire control parameters. A Box-Behnken design was employed to establish a response surface model for optimizing prevention and control strategies. The results show that CH4 levels near the upper corner initially decline as extraction deepens but later rise. Higher extraction quantities are found to be counterproductive in preventing coal spontaneous combustion. The optimal configuration for synergistic prevention includes: extraction at 28.662 m from the working face with a flow quantity of 87.560 m3/min and nitrogen injection at 54.895 m with a flow rate of 827.511 m3/h. These parameters result in a predicted oxidation zone area of 8769 m2 and a CH4 concentration of 0.534 %. Field implementation confirmed the effectiveness of this scheme in reducing the risk of coupled disasters, offering valuable guidance for safe mine withdrawal.